Genetic variability and association analysis for yield and yield components in indigenous and exotic collections of vetiver (Vetiveria zizanioides (L.) Nash) - Lal, R K (Journal of Spices and Aromatic Crops, 2000)
The variability in genetic parameters and their influence on growth and yield of vetiver (Vetiveria zizanioides) was studied in 45 indigenous and exotic collections. Considerable variability in morphometric traits was recorded in these collections. Strongly positive and significant correlations were found between plant height and root length and oil yield; root length and oil content; fresh root yield and dry root yield and oil yield; dry root yield and oil yield, and oil content and oil yield. Positive and significant associations were also observed between plant height and root width and fresh root yield; root length and root width. These traits may form a good selection criteria for improvement of essential oil yield in vetiver.